Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5194/bg-9-4897-2012
|View full text |Cite
|
Sign up to set email alerts
|

An eddy-stimulated hotspot for fixed nitrogen-loss from the Peru oxygen minimum zone

Abstract: Abstract. Fixed nitrogen (N) loss to biogenic N 2 in intense oceanic O 2 minimum zones (OMZ) accounts for a large fraction of the global N sink and is an essential control on the ocean's N-budget. However, major uncertainties exist regarding microbial pathways as well as net impact on the magnitude of N-loss and the ocean's overall N-budget. Here we report the discovery of a N-loss hotspot in the Peru OMZ associated with a coastally trapped mesoscale eddy that is marked by an extreme N-deficit matched by bioge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
80
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 42 publications
11
80
3
Order By: Relevance
“…The upper N* minimum, which is located above the OMZ, is most probably a residual of the uplifted PCU during its upwelling at the shelf. This is in contrast to the interpretations of Altabet et al (2012) who argued that the upper N* minimum observed in a comparable anticyclonic coastal eddy off Peru resulted from shelf waters that had been in contact with shelf sediments and thus were carrying signals of sedimentary dentrification and/or anammox (Altabet et al, 2012).…”
Section: The Cyclonic Feature (Eddy C)contrasting
confidence: 52%
See 4 more Smart Citations
“…The upper N* minimum, which is located above the OMZ, is most probably a residual of the uplifted PCU during its upwelling at the shelf. This is in contrast to the interpretations of Altabet et al (2012) who argued that the upper N* minimum observed in a comparable anticyclonic coastal eddy off Peru resulted from shelf waters that had been in contact with shelf sediments and thus were carrying signals of sedimentary dentrification and/or anammox (Altabet et al, 2012).…”
Section: The Cyclonic Feature (Eddy C)contrasting
confidence: 52%
“…A similar feature is seen in the O 2 and NO Barber and Huyer, 1979;CopinMontégut and Raimbault, 1994;Fernández et al, 2009;Altabet et al, 2012;Casciotti et al, 2013) Codispoti et al (1986).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations